2003
DOI: 10.1161/01.cir.0000097000.51723.6f
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and Not Plasminogen Activator Inhibitor-1 Is a Critical Mediator of Early Angiotensin II/ N G -Nitro- l -Arginine Methyl Ester-Induced Myocardial Injury

Abstract: Background-Angiotensin II (Ang II) increases levels of aldosterone and plasminogen activator inhibitor-1 (PAI-1). Both aldosterone and PAI-1 seem to promote cardiovascular (CV) injury. Our objective was to determine the roles of PAI-1 and aldosterone in the development of myocardial and renal damage in a model with high Ang II and low nitric oxide (NO) availability, a pattern seen in patients with heart failure, diabetes mellitus, and arteriosclerosis. Methods and Results-Mice on a moderately high sodium diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 39 publications
8
89
1
Order By: Relevance
“…Our laboratory has previously shown that a chronic HS diet in WT mice or in rats is not associated with cardiac tissue damage (21,26,30,37). We hypothesized that Cav-1 deficiency during the HS diet may affect eNOS expression and/or activity, not only in the blood vessels, but also in the heart.…”
Section: Discussionmentioning
confidence: 95%
“…Our laboratory has previously shown that a chronic HS diet in WT mice or in rats is not associated with cardiac tissue damage (21,26,30,37). We hypothesized that Cav-1 deficiency during the HS diet may affect eNOS expression and/or activity, not only in the blood vessels, but also in the heart.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings support the studies of others showing that MR mediates vascular inflammation. For example, the MR antagonists decrease oxidative stress and vascular inflammation in animal models (17)(18)(19)(20)(21)44).…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone infusion induces leukocyte infiltration into arteries of rats and increases the expression of proinflammatory markers (15,16). Mineralocorticoid receptor (MR) antagonists decrease monocyte infiltration into the vascular wall in hypertensive rats, in rats treated with aldosterone, and in hypertensive mice (17)(18)(19)(20)(21). Clinical studies also show that aldosterone increases markers of vascular inflammation.…”
mentioning
confidence: 99%
“…Systolic BP was assessed by tail-cuff plethysmography on day 6, prior to the animals being killed as previously reported (Martinez et al 2002, Oestreicher et al 2003, Pajoga et al 2010.…”
Section: Bp Measurementsmentioning
confidence: 99%
“…Caveolae and their associated proteins (caveolins) and striatin, a caveolinassociated protein, were recently shown to mediate the non-genomic actions of steroids (Lu et al 2004) and to participate in activation of signaling transduction pathways of membrane receptors, including steroid receptors and type 1 angiotensin II receptor (AT 1 R; Ushio-Fukai et al 2005. We also assessed extracellular signal-regulated kinase (ERK) activity and plasminogen activator inhibitor-1 (PAI-1) as these factors are activated by both ANGII and aldosterone and have adverse effects on the heart (Oestreicher et al 2003). Finally, the effects of sodium intake on cardiac endothelial nitric oxide synthase (eNOS) activity were assessed as NO has beneficial CV effects that could counter the adverse effects of ANGII/ aldosterone.…”
Section: Introductionmentioning
confidence: 99%